UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR SISWA MATA PELAJARAN FIQIH DI SMP ISLAM KARANGPLOSO MALANG - Zaimatun Ni’mah; Ika Ratih Sulistiani; Ika Anggraheni (VICRATINA, 2019)
This research is motivated by the condition of Al-Rifa'ie High School students who currently have some unskilled students communicating well in learning activities so that the learning outcomes obtained are not optimal, for example there are unskilled students who ask when they do not understand the subject matter given the teacher, when given the opportunity to answer by the teacher, students cannot answer questions correctly, clearly, and smoothly. Therefore, researchers want to do research to find out how the actual conditions of communication skills of students when learning, especially on Islamic Education subjects. This research is a quantitative research with research methods applied is descriptive method. In collecting data, researchers used the necessary research instruments, namely using a questionnaire and interviews. Analysis of each instrument that has been distributed, shows that the level of communication skills of students in the medium category. This is evident from the answers of students who are more focused on neutral answers, in the sense that these students are not so high in their communication skills, nor are their communication skills too low on PAI subjects. So they tend to be normal towards PAI subjects, their communication skills towards PAI subjects at a moderate level.